45S5 Bioactive Glass-Ointment Positively Effects on Wound Healing in Rats by Regulating TNFα, Il-10, VEGF, and TGFβ - Kirgiz, Omer; Altug, Muhammed Enes; Ozkan, Huseyin; Han, Mehmet Cengiz; Akcakavak, Goekhan; Ozarslan, Ali Can; Yucel, Sevil (WILEY, 2024)
AimThis study aimed to investigate the effects of 45S5 bioactive glass-ointment (BG) on cutaneous wound healing in rats at the molecular, biochemical, and histopathological levels.Materials and MethodsThirty-two rats were divided into four groups (n = 8): Control, Sham, BG, and DEX (Dexpanthenol). While no wound treatment was applied to the CONTROL, a wound model was created in the Sham, and no treatment was applied. A wound model was created for other groups, and BG and DEX were applied locally for 21 days. During the 21-day experiment period, feed and water consumption and weight changes were observed. Wound areas were calculated on days 0, 3, 7, 4, and 21. Following treatment, the rats were euthanized and tissues from the wound area and blood samples were collected. While the expression levels of tumor necrosis factor-alpha (TNF alpha), Interleukin 6 (IL6), Interleukin 10 (IL10), transforming growth factor-beta (TGF beta), and vascular endothelial growth factor (VEGF) genes were determined by qPCR, the levels of TNF alpha, IL6, and IL10 proteins were measured by ELISA.ResultsIt was observed that the BG group showed anti-inflammatory activity by suppressing TNF alpha levels and stimulating IL-10. In addition, it was determined that BG increased fibroblast activity and vascularization.ConclusionCurrent findings showed that topical application of BG has anti-inflammatory effects, while also accelerating healing by increasing vascularity and making positive contributions to tissue healing. This study investigates the effects of topical application of 45S5 bioactive glass-ointment (BG) on wound healing in rats at the molecular and histopathological levels. The findings demonstrate that BG exhibits anti-inflammatory activity, enhances vascularization, accelerates healing, and contributes positively to tissue repair.image
Keywords: bioactive glasses; ELISA; gene expression; histopathology; wound healing; MACROPHAGES; EXPRESSION; Medical Laboratory Technology